From social to informational exclusion: how othering shapes acculturation trajectories and health information access among international students - Brill, Janine; Karnowski, Veronika; Rossmann, Constanze (Frontiers in Communication, 2025)
IntroductionIn recent years, Germany has experienced a steady rise in international student enrollment at its higher education institutions. While universities publicly commit to diversity, equity, and inclusion (DEI) principles, many fall short in translating these commitments into concrete practices. The lack of initiatives fostering meaningful cross-cultural engagement frequently contributes to integration challenges and experiences of othering. These experiences cause international students to face greater adjustment challenges than their local peers, often resulting in increased feelings of loneliness, depression, and isolation. Limited social interaction and othering can further create barriers in accessing health information and services. In this challenging time, however, it is particularly important to have access to health information and services that support and advise international students in coping with emotional and social difficulties. Drawing on social capital theory, this study examines the interrelationship between international students’ experiences of othering, their ties within their country of origin and Germany—reflected in their acculturation trajectories—and access to health information.MethodsTo examine these interrelations and the role of othering in these processes, we conducted interviews with 15 international students in Germany.ResultsThe findings indicate that acculturation trajectories are reflected in participants’ health information repertoires, particularly regarding access to trusted individuals as health information sources. Participants undergoing integration typically reported utilizing a broader set of sources from multiple cultural contexts, whereas those experiencing separation or assimilation tended to rely on sources from only one context. Experiences of social othering—particularly within university settings—shaped the international students’ acculturation trajectories, especially among those experiencing separation. Linguistic exclusion and discriminatory behaviors by health professionals prompted many participants to avoid medical consultations and instead rely more on online sources.DiscussionThese findings underscore the need for cultural sensitivity training among health professionals and institutional efforts to counteract othering on campus through comprehensive integration strategies and cross-cultural engagement initiatives.